PEMANFAATAN UT-ONLINE OLEH MAHASISWA UNIVERSITAS TERBUKA - Sugilar Sugilar (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2014)
UT-Online is one of the internet-based student services offered by the Open University (UT) to all students. This study aims to analyze, first, the characteristics of students UT-Online users; second, knowledge of the existence of UT student-Online for each service provided in the UT-Online; Third, the behavior of the students in the use of UT-Online; and the fourth assessment of the benefits of UT student-Online. Survey is the method used in this study that managed to capture the information of 904 students through electronic mail. From this study found important matters as the following, first, the characteristics of students UT UT-Online users related to intensity of use UT-Online is the ease of accessing the internet, age, and sex, and there is a tendency that the number of UT-Online users increases with increasing student enrollment year. Secondly, each facility UT-Online has recognition rate, the use, possession, and diverse training needs. Third, each facility UT-Online can be classified based on the number of users, frequency of use, and time of access by students. Fourth, the benefit of UT-Online scores assessed the level of positive attitude of students toward the facility in the UT-Online. Related to the findings, the researchers recommend the things that can improve the quality and usefulness of UT-Online for students. UT-Online merupakan salah satu layanan mahasiswa berbasis internet yang ditawarkan oleh Universitas Terbuka (UT) kepada seluruh mahasiswa. Penelitian ini bertujuan untuk menganalisis, pertama, karakteristik mahasiswa pengguna UT-Online; kedua, pengetahuan mahasiswa terhadap keberadaan UT-Online untuk tiap layanan yang disediakan dalam UT-Online; ketiga, perilaku mahasiswa dalam pemanfaatan UT-Online; dan keempat penilaian mahasiswa terhadap manfaat UT-Online. Survey merupakan metode yang digunakan dalam penelitian ini yang berhasil menjaring informasi dari 904 mahasiswa melalui surat elektronik. Dari penelitian ini ditemukan hal-hal penting sebagai berikut, pertama, karakteristik mahasiswa UT pengguna UT-Online yang berkaitan intensitas pemanfaatan UT-Online ialah kemudahan mengakses internet, usia, dan jenis kelamin, serta terdapat kecenderungan bahwa jumlah pengguna UT-Online meningkat sejalan dengan meningkatnya tahun masuk mahasiswa. Kedua, setiap fasilitas UT-Online memiliki tingkat pengenalan, penggunaan, penguasaan, dan kebutuhan pelatihan yang beragam. Ketiga, setiap fasilitas UT-Online dapat digolongkan berdasarkan jumlah pengguna, frekuensi penggunaan, dan lama akses oleh mahasiswa. Keempat, kemanfaatan UT-Online dinilai dalam skor tingkat sikap positif mahasiswa terhadap fasilitas dalam UT-Online tersebut. Terkait dengan temuan, peneliti merekomendasikan hal-hal yang dapat meningkatkan kualitas dan kemanfaatan UT-Online bagi mahasiswa.